2016
DOI: 10.7314/apjcp.2016.17.3.1141
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Glutathione S-transferase T1 Null Genotype with Risk of Gastric Cancer: a Meta-analysis in Asian Populations

Abstract: Background: A large number of studies have been published to investigate the association between the null genotype of glutathione S-transferase T1 (GSTT1) with gastric cancer. However, the results were inconsistent and conflicting. The aim of this study was to estimate the relationship between this polymorphism in the GSTT1 gene and gastric cancer risk in Asian populations by meta-analysis. Materials and Methods: A literature search was performed in PubMed, Embase, Chinese Biomedical database (CBM), Weipu data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
1
1
1
Order By: Relevance
“…GSTT1 -null combined with smoking might be obviously related to the pathogenesis of prostate cancer and pancreatic cancer for the risk being as high as 2.847 times and 3.749 times, respectively. Although Zeng et al [ 116 ] in 2016 found that alcohol consumption was not a co-factor of GSTT1 -null in the development of gastric cancer, our findings suggested that an increased cancer risks might be associated with smoking (OR = 1.944, P = .045) and drinking (OR = 1.877, P = .021) among GSTT1 -null carriers. In addition, the risk of cancers increased by 1.318-fold and1.543-fold among Caucasian smokers and drinkers, and by 1.701-fold and 2.250-fold among Asian smokers and drinkers, respectively.…”
Section: Discussioncontrasting
confidence: 80%
“…GSTT1 -null combined with smoking might be obviously related to the pathogenesis of prostate cancer and pancreatic cancer for the risk being as high as 2.847 times and 3.749 times, respectively. Although Zeng et al [ 116 ] in 2016 found that alcohol consumption was not a co-factor of GSTT1 -null in the development of gastric cancer, our findings suggested that an increased cancer risks might be associated with smoking (OR = 1.944, P = .045) and drinking (OR = 1.877, P = .021) among GSTT1 -null carriers. In addition, the risk of cancers increased by 1.318-fold and1.543-fold among Caucasian smokers and drinkers, and by 1.701-fold and 2.250-fold among Asian smokers and drinkers, respectively.…”
Section: Discussioncontrasting
confidence: 80%
“…Встречаемость таких делеций в популяциях очень высока, поскольку установлено, что до половины европеоидного населения являются гомозиготами по делеции гена GSTM1 и около 15% по делеции гена GSTT1 [6,13]. В настоящее время, показано, что полиморфизм генов GSTM1 и GSTT1, связанный с делецией этих генов играет важную роль в повышенном риске не только некоторых типов рака [13,19], но и более тяжелого течения инфекционных заболеваний, таких как туберкулез, малярия, ВИЧ-инфекция и геморрагическая лихорадка с почечным синдромом [5,7,12,15].…”
Section: Discussionunclassified
“…However, GC incidence declined more among Asian populations during the study period. Host genetic variation14-16 and/or lifestyle factors17 18 may interact with H. pylori infection prevalence19 20 and have been considered as possible carcinogenic factors leading to Asians having a higher incidence of GC. We also found that black patients' incident GCs were in early grade and early stage, which may result in higher risk of second primary cancer in blacks.…”
Section: Discussionmentioning
confidence: 99%